Bergerak dengan Dua Sayap: Fenomena Gerakan Dakwah dan Politik Hizbut Tahrir di Indonesia Pasca Reformasi - aksa aksa (Rihlah : Jurnal Sejarah dan Kebudayaan, 2020)
This paper explains about the phenomenon of HTI politics and its da’wah movement after reformation. The main problems answered in this paper are: what are the activities of da’wah and political movements of HT in Indonesia?, And how is the form of  HTI da’wah through social media and publications? The writing method used the historical writing method which included four stages (heuristics, literary criticism, interpretation and historiography). The results showed that da’wah and the politics of Hizbut-Tahrir in Indonesia is a mainstream phenomenon from a preaching model and politics in general. HTI has played two orientation movements (preaching and politics) in establishing its influence in Indonesia. The da’wah and political movements appeared ambiguous. In terms of da’wah, the activities were more focused on proposing a single ideology and anti-democracy. But at the same time, taking cover themselves behind the armpit of the country which adheres to the democratic system and the ideology of Pancasila. While in the political perspective, its movement was seen as a half-hearted political movement, claiming to be a political movement, but it did not have a political party and was not involved in the electoral contestation. HTI da'wah was increasingly effective by utilizing media and publications (books, magazines, tabloids, and bulletins). The use of social media as a concrete approach has made social media as a mean of preaching. Tulisan ini menjelaskan tentang fenomena gerakan dakwah dan politik HTI pasca reformasi. Masalah pokok yang dijawab dalam tulisan ini yaitu: bagaimana aktivitas dakwah dan gerakan politik HT di Indonesia?, dan bagaimana bentuk dakwah HTI melalui sosial media dan publikasi?. Metode penulisan mengikuti metode penulisan sejarah yang meliputi empat tahapan (heuristik, kritik sumber, interpretasi dan historiografi). Hasilnya menunjukan bahwa dakwah dan politik Hizbut Tahrir di Indonesia adalah sebuah fenomena mainstream dari model dakwah dan politik umumnya. HTI telah memainkan dua orientasi gerakan (dakwah dan politik) dalam menancapkan pengaruhnya di Indonesia. Gerakan dakwah dan politiknya terlihat ambiguitas. Dari segi dakwah, aktivitasnya lebih terfokus pada pengusulan ideologi tunggal dan anti demokrasi. Tetapi pada saat bersamaan, berlindung diri di balik ketiak negara Indonesia yang menganut sistem demokrasi dan berideologi Pancasila. Sementara dari segi politik, gerakannya terkesan sebagai gerakan politik setengah hati, mengklaim dirinya sebagai gerakan politik, tetapi tidak memiliki partai politik dan tidak terlibat dalam kontestasi pemilu. Dakwah HTI semakin efektif dengan memanfaatkan media dan publikasi (buku, majalah, tabloid, dan bulletin). Pemanfaatan sosial media sebagai langkah kongkrit menjadikan sosial media sebagai sarana dakwah.